KONSEP KEPEMIMPINAN DALAM PERSPEKTIF TEOLOGI SYIAH - Kamaluddin Nurdin Marjuni (Pascasarjana IAIN Sorong, 2020)
Imamah (Leadership of the State) is the main factor causing disputes among Muslims until today, thus splitti ng Islam into various streams, classes and schools. The conflict between Islamic groups aft er the Prophet based on a question: who should and deserve to be the leader of the state. In the Shiite concept known as “Imamah” which mean that Shiite Imamah is not a matter of personal interest given to the general choice, but it is one of the principles and foundati ons of Islamic religious principles (Arkan ad-Din). This paper will explain the implementati on of imamah concept and the conflicts that occur in the issue of political differenti on between Shiite groups. Various problems are analyzed through Shiite primary books. This study shows that Shiite throughout the history of Islamic politics always be a dissident side.